STRATEGI PENGELOLAAN SUMBERDAYA ALAM BERBASIS MASYARAKAT DI TAMAN WISATA ALAM PENELOKAN KABUPATEN BANGLI - BUDIANA, IWAYAN GEDE; Mardani, N.K; SUNARTA, I NYOMAN (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 6 No 2 (2011), 2011)
Natural resources of forests is one of the natural wealth that has a very strategic value. Although these natural resources belong to the category potential of renewable natural (renewable), the management of the natural wealth of this should really be done in a wise, prudent and professional. The purpose of this study to determine the public perception of forest management at Natural Tourism Park (1WA) Penelokan and formulate a strategy of community-based naturalresource conservation in the 1WA Penelokan. Public perception of the spread of the questionnaire obtained by the method of purposive sampling. Further identification of internal and internal factors to formulate conservation strategies by u sing SWOT analysis. The results showed people's perception about the functioning of 1WA Penelokan stated that forests have many functions (multiple functions). Public perception of management policies that 1WA Penelokan community does not know the regulations related to forest management. Public Perception of Institutional Management in Penelokan 1WA stated that they are not part of forest management institutions. Public perceptions of the Rights and Obligations of Civil Society in the Management of 1WA Penelokan society have the perception that forests are publicly owned assets (common property). Community-based conservation strategy that is obtained by optimizing the management of natural resources Penelokan 1WA -based society, optimizing the ecological functions of 1WA Penelokan with community involvement, empowering communities to preserve 1WA Penelokan, optimize community participation in natural resource management 1WA Penelokan, improve education and socialization programs related institutions to the community, improve coordination among stakeholders in the management of 1WA Penelokan, improve the quality of the human resources about the function of 1WA Penelokan, socialize legislation to improve environmental quality, coordinate the relations between stakeholders to pressure changes in the function of forests, increase socialization and coordination to reduce damage forest environments, improve the quality of human resources management agencies in providing socialization and counseling, and optimize the role of stakeholders to suppress the loss of forest land.
Keywords: TWA Penelokan, public perception, management strategies